칼로스 쌀의 유변학적 특성과 이로 제조된 냉동 강황밥의 해동방법에 따른 품질특성 변화 - 김소연(So Yeon Kim); 최유라(Yu Ra Choi); 김경섭(Kyeong Seop Kim); 이상준(Sang Jun Lee); 장윤혁(Yoon Hyuk Chang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
This study investigated the rheological properties of Calrose rice flour dispersions as well as the effects of different thawing methods (steamer, smart oven, and microwave oven) on quality characteristics of frozen turmeric rice. Apparent viscosity, consistency index, and yield stress significantly increased at higher rice flour concentrations. Magnitudes of storage modulus and loss modulus significantly increased with elevation of rice flour concentration. Frozen turmeric rice thawed using a steamer had the highest moisture content and largest size (length, width, and thickness) among all thawing methods. The L values of turmeric rice after thawing using a steamer was significantly higher than those of other thawing methods. The a value of turmeric rice after thawing using a steamer was significantly lower than those of other thawing methods. Textural properties (hardness, adhesiveness, springiness, cohesiveness, brittleness, and chewiness) of frozen turmeric rice after thawing using a steamer were significantly lower than those of other thawing methods. Therefore, it can be concluded that frozen turmeric rice after thawing using a steamer might be desirable for improvement of texture. 본 연구는 칼로스 품종으로 제조한 쌀가루 분산액(3, 6, 9%, w/w)에 따른 유변학적 특성 및 해동방법에 따른 냉동 강황밥의 품질특성에 대하여 평가하였다. 쌀가루 분산액은 전단담화 거동을 나타내었으며, 쌀가루 농도가 증가함에 따라 쌀가루 분산액의 점조도 지수, 겉보기 점도, Casson 항복응력 값이 증가하는 경향을 나타내었다. 쌀가루 분산액의 동적점탄 특성에 의하면 진동수 범위(0.63~62.8 rad/s)에서 진동수가 증가함에 따라 G′과 G″ 값들이 증가하는 경향을 나타내었다. RVA에 의한 쌀가루의 페이스팅 특성은 농도가 증가할수록 peak viscosity, trough viscosity, final viscosity, breakdown viscosity, setback viscosity 값이 증가하였다. 재가열 조건에 따른 냉동 강황밥의 수분함량은 스팀기, 스마트오븐, 전자레인지로 해동한 순으로 유의적으로 높았다. 색도 측정 결과 L값은 스팀기가 유의적으로 높은 값을 보였다. a값은 음의 값을 보였으며, 스팀기에서 가장 낮았고 전자레인지에서 가장 높은 값을 보였다. b값은 전자레인지가 가장 높은 값을 보였으며, 스팀기와 스마트오븐은 유의적으로 차이가 없었다. 기계적 텍스처 특성 분석 결과 경도, 부착성, 탄력성, 응집성, 깨짐성, 씹힘성 모든 값에서 스팀기가 유의적으로 낮은 값을 보였다. 결과적으로 스팀기를 이용하여 해동한 냉동 강황밥이 가장 부드러운 조직감을 보였다.